IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) BERBASIS PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Abelda Fauzia Sasabela; Wahyu Rochmadi, Nur; Mila Amiati, Endah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low active involvement and learning outcomes of class X students of SMK Negeri 2 Malang in the Bhinneka Tunggal Ika material, shown by the average pre-cycle score of 70.00 with a classical completeness of 0% against KKM 80. This Classroom Action Research (PTK) aims to describe the implementation of the Project Based Learning (PjBL) model combined with a deep learning approach and test its effectiveness in improving student learning outcomes. The research subjects were 36 students of the Nursing and Caregiving Support Services (LPKC) expertise program. Data were collected through observation, written tests, and documentation, then analyzed descriptively with qualitative and quantitative approaches in two action cycles. The results showed a consistent increase: the average score increased from 70.00 (0% complete) in the pre-cycle to 73.00 (41.67% complete) in the first cycle, and reached 84.50 (100% complete) in the second cycle, accompanied by an increase in motivation, group cooperation, and the courage of students in conveying their aspirations. The combination of PjBL and deep learning has proven to be effective in optimizing learning outcomes and active involvement of students in diversity materials.